THE PETROGENESIS OF CARBONIFEROUS-PERMIAN DYKE AND SILL INTRUSIONS ACROSS NORTHERN EUROPE - Kirstein L.A.; Davies G.R.; Heeremans M. (My University, 2006)
The presence or absence of a thermally anomalous mantle plume during the formation of the widespread Carboniferous-Permian magmatism of northern Europe is examined. The geochemistry of representative samples from the extensive Carboniferous-Permian dyke and sill intrusions across northern Europe are reported in order to ascertain whether they have a common 'plume' source. Both tholeiitic and alkaline magmas have diverse trace element compositions. Alkaline samples with relatively low Ti and Nb/La < 1 are considered to originate in the lithospheric mantle and those with Nb/La > 1 from the asthenosphere. The tholeiites have a close affinity to E-MORB but have mixed with variable amounts of lithosphere and upper crust. Tectonic reorganisation and decompression melting of a trace element-enriched mantle is considered to have controlled the Carboniferous-Permian magmatism, which contains no coherent geochemical evidence for a single plume-related thermo-chemical anomaly. © Springer-Verlag 2006.
Keywords: Палеозой::Пермская; Палеозой::Каменноугольная; Paleozoic::Permian; Paleozoic::Carboniferous